2022
DOI: 10.3390/ijms24010299
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Isorhamnetin and Isorhamnetin Conjugates

Abstract: Isorhamnetin is a plant-derived secondary metabolite which belongs to the family of flavonoids. This review summarises the main outcomes described in the literature to date, regarding the effects of isorhamnetin on obesity from in vitro and in vivo studies. The studies carried out in pre-adipocytes show that isorhamnetin is able to reduce adipogenesis at 10 μM or higher doses and that these effects are mediated by Pparγ and by Wnt signalling pathway. Very few studies addressed in rodents are available so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The anti-adipogenic properties of KH may be contributed by the active components within. Isorhamnetin, which is a metabolite of the flavonoid group quercetin, is known for its anti-adipogenicity [ 63 ]. Studies carried out in vitro have found that incubation of preadipocyte 3T3-L1 with isorhamnetin saw inhibition in the adipogenesis at dose > 10µM [ 29 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-adipogenic properties of KH may be contributed by the active components within. Isorhamnetin, which is a metabolite of the flavonoid group quercetin, is known for its anti-adipogenicity [ 63 ]. Studies carried out in vitro have found that incubation of preadipocyte 3T3-L1 with isorhamnetin saw inhibition in the adipogenesis at dose > 10µM [ 29 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Isorhamnetin, a naturally occurring flavonoid compound discovered in various plants, including fruits, vegetables, and medicinal herbs, has been reported to exhibit a wide range of biological activities, such as antioxidant, anti‐inflammatory, anticancer, antidiabetic, and cardiovascular protective effects (González‐Arceo et al, 2022; W.‐Q. Li, Li, et al, 2022).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%